Enantioselective analysis of citalopram and demethylcitalopram in human whole blood by chiral LC–MS/MS and application in forensic cases. Issue 10 (7th April 2017) - Johansen, Sys Stybe
Abstract : Citalopram is one of the most frequently used antidepressants in Denmark. It is marketed as a racemic mixture (50:50) of S‐ and R‐enantiomers as well as of the S‐enantiomer alone, which is the active enantiomer named escitalopram that processes the inhibitory effects. In this study, a chiral liquid chromatography–tandem mass spectrometry (LC–MS/MS) method is developed for the measurement of citalopram and demethylcitalopram enantiomers in whole blood and is applied to forensic cases. Whole blood samples (0.10 g) were extracted with butyl acetate after adjusting the pH with 2 M NaOH. The analytes were separated on a 250 × 4.6 mm Chirobiotic V, 5 μm column by isocratic elution with methanol:ammonia:acetic acid (1000:1:1) using an ultra‐high‐pressure liquid chromatography (UHPLC) system. Quantification was performed by tandem mass spectrometry (MS/MS) using multiple reaction monitoring (MRM) in the positive mode. The total chromatographic run time was 20 min. The limit of detection (LOD) and quantification (LOQ) were 0.001 and 0.005 mg/kg of all four enantiomers, respectively. Linear behaviour was obtained for all four enantiomers from LOQ to 0.50 mg/kg blood with absolute recoveries from 71 to 80%. The method showed an acceptable precision and accuracy as the obtained coefficient of variation, and bias values were ≤16% for all enantiomers. After the validation of the method, a correlation with the racemic method was assessed and found to be acceptable. Then, the method was successfully applied to authentic blood samples from forensic investigations demonstrating that escitalopram was less frequent than citalopram among all forensic cases. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : A chiral liquid chromatography‐tandem mass spectrometry (LC‐MS/MS) method is developed for the measurement of citalopram and demethylcitalopram enantiomers in whole blood and applied to forensic cases. 7% of the positive citalopram cases would be toxicological misinterpretated if chirality was not determined.